Effect Of Husband's Support On Pregnant Women's Compliance With Antenatal Care At Purwodadi 1 Community Health Center - Dewi Sapta Wati; Wahyu Utami Ekasari; Risa Novitasari Lidya Putra (LPPM AN NUUR, 2023)
Background : One of the goals of health efforts for pregnant women is to ensure the health of the mother and fetus through efforts to reduce maternal and newborn mortality rates. : The existence of problems in pregnant women, such as complications that can endanger the safety of pregnant women, is often caused by pregnant women not making Antenatal Care (ANC) visits. This can be seen from the failure to fulfill the K4 Coverage target in the Central Java region such as Grobogan Regency, 90.2%. Meanwhile, in 2023, there will be a K1–K4 Drop Out (DO) of 4.5 percent. This means that there are still 4.5 percent of pregnant women who do not receive fourth-term antenatal care. Purwodadi I Community Health Center, which is one of the Community Health Centers in Purwodadi District, Grobogan Regency, has low Antenatal Care (ANC) visits in 6th place, namely, the coverage of K4 visits in 2023 is felt to be still less than the set target of 95%. The lack of Antenatal Care is influenced by the lack of husband's support in terms of emotional support, facilities, information and appreciation, causing pregnant women to be disobedient in carrying out antenatal care during pregnancy.Purpose: To determine the effect of husband's support on pregnant women's compliance with antenatal care Method: This research is a quantitative study using an observational analytical survey with a cross sectional approach. The study population was 98 third trimester pregnant women. The sample technique used accidental sampling with 46 respondents. Results: In this study, there is a relationship between husband's support and compliance with antenatal care examinations for pregnant women at the Purwodadi I Community Health Center in 2023, with a P value = 0.001. There are sub variables in this research, namely there is a relationship between emotional support (P value = 0.001), instrumental support (P value = 0.007), and appreciation support (P value = 0.034) with compliance with antenatal care examinations for pregnant women at the Purwodadi Community Health Center I Year 2023. Meanwhile, there is no relationship between informational support and compliance with antenatal care examinations in pregnant women with a P value of sign = 0.053. Conclusion: The results of this study conclude that husband's support consisting of emotional support, instrumental support, informational support, and appreciation support plays a role in increasing pregnant women's compliance with antenatal care. Health workers are advised to provide explanations and increase information about the importance of complying with ANC examinations during pregnancy at least four times. Husbands are also expected to provide extra support to pregnant women, such as providing the necessities needed during pregnancy and accompanying the mother when visiting ANC